1998
DOI: 10.1124/mol.54.3.577
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Hydroxytryptamine6Receptor-Selective radioligand [3H]Ro 63–0563 Labels 5-Hydroxytryptamine Receptor Binding Sites in Rat and Porcine Striatum

Abstract: Ro 63-0563 [4-amino-N-(2,6 bis-methylamino-pyridin-4-yl)-benzene sulfonamide] is a high affinity 5-hydroxytryptamine6 (HT6) receptor antagonist with more than 100-fold selectivity for the 5-HT6 receptor compared with 69 other receptors and binding sites. The present study describes the properties of [3H]Ro 63-0563, the first selective 5-HT6 receptor radioligand. Specific binding of [3H]Ro 63-0563 (nonspecific binding defined in the presence of 10 microM methiothepin) to recombinant rat and human 5-HT6 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 14 publications
3
41
1
Order By: Relevance
“…The distribution of receptor protein in the rat brain as determined by immunocytochemistry Gerard et al, 1996] is in good agreement with the mRNA results. The distribution pattern has been further confirmed by autoradiographic studies using selective ligands [Boess et al, 1998;Hirst et al, 2003;Roberts et al, 2002]. 5-HT 6 receptor distribution in human brain parallels that found in rats Hirst et al, 2003;Kohen et al, 2001].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The distribution of receptor protein in the rat brain as determined by immunocytochemistry Gerard et al, 1996] is in good agreement with the mRNA results. The distribution pattern has been further confirmed by autoradiographic studies using selective ligands [Boess et al, 1998;Hirst et al, 2003;Roberts et al, 2002]. 5-HT 6 receptor distribution in human brain parallels that found in rats Hirst et al, 2003;Kohen et al, 2001].…”
Section: Introductionsupporting
confidence: 57%
“…1) including 5-HT 1, 5-methoxytryptamine 2, LSD 3, methysergide 4, metergoline 5, and methiothepin 8, bind to the 5-HT 6 with high affinity (Fig. 1) as do a number of typical and atypical antipsychotic agents including clozapine 6, loxapine 7, and ritanserin 11 and tricyclic antidepressants such as mianserin 9 and amitryptyline 10 [ Boess et al, 1998;Monsma et al, 1993;Roth et al, 1994]. The binding affinity of these compounds is very similar among different species including human, rat, and mouse ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the 5-HT6 receptor in artificial expression systems (Ruat et al, 1993) and striatal tissues (Boess et al, 1998) enhances adenylate cyclase activity. In situ hybridization (Gerard et al, 1996) and immunohistochemical studies (Gerard et al, 1997) demonstrate that 5-HT6 receptors are abundant in DA terminal areas including the striatum, NA, hippocampus, and frontal cortex.…”
Section: -Ht6 Localizationmentioning
confidence: 99%
“…Tissue-section receptor autoradiography studies have characterized the binding and distribution of the radioligands 125 I-SB-258585 and 3 H-Ro-63-0563 in various species (9,10). These studies have consistently revealed heterogeneous binding throughout the brain, with the highest levels found in the striatum, moderate levels in the cerebral cortex, and the lowest levels in the cerebellum.…”
mentioning
confidence: 99%